Nearshore wave analysis of Batu Pahat river estuary - Norazlina, Bateni. (UNIMAS, 2008)
Estuary, like other coastal systems, is ephemeral; undergo continuous geological evolution and very active coastal region. In this study, Batu Pahat river estuary is chosen, to observe wave conditions near shore.Estuary of Sungai Batu Pahat is facing critical erosion due to navigation channel and exposed to high energy wave conditions from the Strait of Melacca. The offshore wave data are analyzed for various design waves of average one third of maximum wave heights (H1/3) and extreme value of Gumbel and Weibull statistical distribution with three wave scenarios of Annual, Northeast Monsoon and Southwest Monsoon. This was followed by calculation of wave transformation near shore using linear wave theory of Regular Wave theory and SWAN (Simulation Wave Nearshore) modeling formulated from Irregular Wave theory of spectral method. Gumbel statistical distribution predicted higher wave height near shore compared to Weibull statistical distribution. H1/3 gives the smallest. Then, in SWAN analysis results of finer grid size of 25m x 25m and coarse grid size of 50m x 50m grid size were compared. Finer grid size gave smaller results of wave heights at the same depth of coarse grid size. Furthermore, bathymetry of Sungai Batu Pahat is digitized and interpolated using SURFER program to provide with dredging and reclamation effects at the site. The bathymetry data was then exported to SWAN as SWAN bottom data. Dredging and reclamation activities had affected wave condition nearshore. Wave height, period, direction and energy dissipation is increased at nearshore area when compared to without dredging and reclamation effects. Thus, nearshore wave analysis had been successfully determined for various conditions and scenarios at Batu Pahat river estuary.